Ideal nodal net phonons in Pn3¯m type Ag2O - Li, Yang (Frontiers in Physics, 2023)
The topological phonon state is a new field that has sparked much interest. Weyl phonons in FeSi, for example, have been theoretically proposed and experimentally identified. In this work, via the first-principle calculation, we prove the ideal nodal net phonons exist in a realistic material Ag2O with type structure. With the help of the Berry phase calculations, we find that the nodal net phonons in Ag2O are topologically nontrivial. The phononic surface states are visible, which benefits the experimental detections. The results in this work contribute to the material realization of topological nodal net phonons. The author hopes the experimental verification of the novel topological phonons can be done in the following investigations.